EXPLORING EDUCATIONAL LEADERS’ PERCEPTION ON THE FEASIBILITY OF OFFERING PEACE EDUCATION: A CASE STUDY - Abd Razak, Afareez; Khairuddin, Ahmad Zulfadhli; Idrus, Faizah (2016)
In any countries, the word peace is essential to maintain its sovereignty and its survival. Without peace the world is in anarchy. Malaysia is a land consists of multi-racial individuals and family that live side by side in many years after her independence in 1957. Thus, it is essential for its citizen to practice peace culture and peace education that focuses on creating a sustainable environment to enable the citizens to interact with each other regardless of political background, ideologies, religious beliefs and practices. The purpose of this study is to explore the perceptions of educational leaders in Klang, Selangor on how peace education could be included in the school curriculum. This study has adopted a qualitative design, and semi-structured interview technique has been employed as the data collection tool. 3 out of 5 educational leaders have voluntarily participated in this study. Findings suggested that all of the respondents reported that they mutually agreed to include peace education as part of the curriculum to maintain harmony, inculcate tolerance among students, minimize conflicts and know their country‟s history. Obstacles and challenges in introducing peace education as a subject can be minimized pertaining to implementation of costs and teacher training. Lack of expertise and lack of interest among students are identified as another challenge to introduce peace education. Furthermore, educational leaders were found to have low levels of awareness, knowledge, and skills related with peace education.